Adsorption of norfloxacin from aqueous solution on biochar derived from spent coffee ground: Master variables and response surface method optimized adsorption process. (February 2022) - Nguyen, Van-Truc; Vo, Thi-Dieu-Hien; Nguyen, Thanh-Binh; Dat, Nguyen Duy; Huu, Bui Trung; Nguyen, Xuan-Cuong; Tran, Thanh; Le, Thi-Ngoc-Chau; Duong, Thi-Giang-Huong; Bui, Manh-Ha; Dong, Cheng-Di; Bui, Xuan-Thanh
Abstract: In this study, biochar derived from spent coffee grounds (SCGB) was used to adsorb norfloxacin (NOR) in water. The biochar properties were interpreted by analysis of the specific surface area, morphology, structure, thermal stability, and functional groups. The impacts of pH, NOR, and ion's present on SCGB performance were examined. The NOR adsorption mode of SCGB is best suited to the Langmuir model (R 2 = 0.974) with maximum absorption capacity (69.8 mg g −1 ). By using a Response Surface Method (RSM), optimal adsorption was also found at pH of 6.26, NOR of 24.69 mg L −1, and SCGB of 1.32 g L −1 . Compared with biochars derived from agriculture such as corn stalks, willow branches, potato stem, reed stalks, cauliflower roots, wheat straw, the NOR adsorption capacity of SCGB was 2–30 times higher, but less than 3–4 times for biochars made from Salix mongolica, luffa sponge and polydopamine microspheres. These findings reveal that spent coffee grounds biochar could effectively remove NOR from aqueous solutions. Approaching biochar derived from coffee grounds would be a promising eco-friendly solution because it utilizes solid waste, saves costs, and creates adsorbents to deal with emerging pollutants like antibiotics. Graphical abstract: Image 1 Highlights: Norfloxacin was removed using biochar derived from spent coffee grounds (SCGB). pH significantly influenced the Norfloxacin (NOR) adsorption of the SCGB. Based on Langmuir model, the maximum absorption capacity was 69.8 mg g −1 at pH 6. The adsorption process was optimized by using the response surface methodology. Optimal adsorption conditions were achieved at pH of 6.26 and SCGB of 1.32 g L −1 .